EVALUASI KEBIJAKAN DISIPLIN SANTRI DI PONDOK PESANTREN AL-HAROMAIN: PERSPEKTIF MODEL CIPP (CONTEXT, INPUT, PROCESS, PRODUCT) - Halimatus Sadi'yah; Titin Nurhidayati; Imam Bahauddin (As-Sulthan Journal of Education, 2026)
This research is motivated by the suboptimal implementation of student discipline policies in Islamic boarding schools (pesantren), despite being conceptually designed to foster character and discipline based on Islamic values. This study aims to evaluate student discipline policies and identify factors influencing their effectiveness. The method used was a qualitative case study approach, with data collection techniques including in-depth interviews, observation, and documentation of caregivers, administrators, religious teachers, and students. Data analysis was conducted using the Miles and Huberman interactive model with the CIPP (Context, Input, Process, Product) evaluation framework. The results indicate that while the discipline policies have relevant objectives, their implementation has been suboptimal due to weak policy communication, limited resources, inconsistent enforcement, and the absence of clear standard operating procedures. Consequently, changes in student behavior have been uneven, and repeated violations are still found. This study concludes that the success of discipline policies is largely determined by the quality of implementation, thus necessitating strengthening aspects of governance, consistency, and internalization of spiritual values ​​in fostering student discipline.